BRUTUS and its paralogs, BTS LIKE1 and BTS LIKE2, encode important negative regulators of the iron deficiency response in Arabidopsis thaliana. Issue 7 (16th June 2017) - Hindt, Maria N.; Akmakjian, Garo Z.; Pivarski, Kara L.; Punshon, Tracy; Baxter, Ivan; Salt, David E.; Guerinot, Mary Lou
Abstract : BTS family members negatively regulate the Fe deficiency response; mutants have increased Fe levels and tolerance to Fe deficiency. Abstract : Iron (Fe) is required for plant health, but it can also be toxic when present in excess. Therefore, Fe levels must be tightly controlled. The Arabidopsis thaliana E3 ligase BRUTUS (BTS) is involved in the negative regulation of the Fe deficiency response and we show here that the two A. thaliana BTS paralogs, BTS LIKE1 ( BTSL1 ) and BTS LIKE 2 ( BTSL2 ) encode proteins that act redundantly as negative regulators of the Fe deficiency response. Loss of both of these E3 ligases enhances tolerance to Fe deficiency. We further generated a triple mutant with loss of both BTS paralogs and a partial loss of BTS expression that exhibits even greater tolerance to Fe-deficient conditions and increased Fe accumulation without any resulting Fe toxicity effects. Finally, we identified a mutant carrying a novel missense mutation of BTS that exhibits an Fe deficiency response in the root when grown under both Fe-deficient and Fe-sufficient conditions, leading to Fe toxicity when plants are grown under Fe-sufficient conditions.